Esensi Penyelesaian Konflik Tanah Hak Ulayat Masyarakat Hukum Adat Pada Perusahaan Penanaman Modal Asing - Amiruddin, Amiruddin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This research aims to understand, analyze, and describe the essence of resolving land rights conflicts of indigenous law communities in foreign investment companies. The study uses normative legal research, empirical legal research (numerical), and historical studies as comprehensive supplementary data. This type of research was chosen because the conflicts have been ongoing for a long time, and various resolution efforts have been made, but none have comprehensively resolved the conflicts. The research was conducted on indigenous law communities experiencing land rights conflicts with foreign investment companies, using descriptive analytical methods derived from qualitative and quantitative data on land rights conflicts of indigenous law communities and the existence of foreign investment companies. The research findings indicate that the essence of resolving land rights conflicts of indigenous law communities in foreign investment companies, whether through litigation or non-litigation, has not successfully resolved the conflicts comprehensively. This has led to legal and social uncertainty. The recommendation is that the essence of resolving land rights conflicts of indigenous law communities with foreign investment companies requires an independent initiator with high integrity, morals, and an understanding of conflict typologies without being influenced by practical political interests. Furthermore, there is a need for government support to foster a spirit of diversity by accommodating indigenous law communities as a protected communal entity under the law.